Metal removal from industrial wastewater by a novel carbon nanomaterial. - Onundi, Yusuf Bamidele; Al-Mamun, Abdullah; Al-Khatib, Ma An Fahmi Rashid; Ahmed , Yehya M. (2009)
Recent application of nanomaterials as adsorbent for heavy metals removal has shown remarkable results which is largely due their mechanical and physical properties. In this work, feasibility of using novel carbon nanomaterials as adsorbent for the removal of copper, nickel and lead ions from an industrial wastewater by the adsorption process was investigated. The adsorbent used was a composite carbon nanomaterials (CNMs) grown on substrate granular activated carbon (GAC) made from Palm Kernel shell (PKS) of mesh size 8x12.Characterization of the adsorbent was carried out using FESEM, TEM. The effect of pH and adsorbent dosage on metals uptake from solution was investigated. The results showed successful growth of CNMs on the GAC, the adsorption of lead, copper and nickel metals ions was best at pH 5, while maximum capacity was recorded at 1 g/L dosage of adsorbent for lead and copper while nickel was at 2 g/L. The order of affinity for the metals ions by the adsorbent was Pb> Cu >Ni.